Quantifying multiple threats to endangered species: an example from loggerhead sea turtles. Issue 5 (28th May 2010) - Bolten, Alan B; Crowder, Larry B; Dodd, Mark G; MacPherson, Sandra L; Musick, John A; Schroeder, Barbara A; Witherington, Blair E; Long, Kristy J; Snover, Melissa L
Abstract : The effectiveness of recovery plans for threatened and endangered species has been questioned in academic and political domains. A comprehensive assessment of species recovery plans concluded that quantification and prioritization of threats have received insufficient attention, which contributes to the failure of some plans. On the basis of this assessment, we developed and implemented a detailed analysis of threats in the Recovery Plan for the Northwest Atlantic Population of the Loggerhead Sea Turtle (Caretta caretta ), produced by the National Marine Fisheries Service and US Fish and Wildlife Service. The analytical approach that we designed and summarize here provides an objective process for quantifying known threats and prioritizing recovery actions in terms of their relative impact on population growth rate (λ) of the loggerhead sea turtle. Although this process was developed for loggerhead sea turtles, it can be applied to other species.